2014
DOI: 10.1111/ijau.12031
|View full text |Cite
|
Sign up to set email alerts
|

Auditor–Client Interactions in the ChangedUKRegulatory Environment – A Revised Grounded Theory Model

Abstract: Audit and financial reporting quality are under intense scrutiny nationally and globally. The outcome of high-level auditor-auditee discussion and negotiation issues (auditorclient interactions) is central to this debate. Beattie et al. (2001) developed a grounded theory model of these interactions in the 1997 UK setting. This paper reports on a field study of 45 interactions in nine case companies in the radically changed post-SOX regulatory environment. Crucially, interviewees in each case company extend the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…By providing findings on the ways in which audit committees are engaged in auditor planning, the study's results, by way of a Critical Discourse Analysis of CGRs, contrast with Beattie et al (), who found that audit committees were not satisfactorily engaged in auditor planning. In Beattie et al (), the audit committee chair has specific monitoring responsibilities over the CFO and auditor, but in the narratives presented in the CGRs studied the audit committee chair is not delineated as having specific prominence in the auditor and audit committee interactions. Instead, such interactions in these Swedish companies are disclosed as taking place between the whole audit committee and the auditor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By providing findings on the ways in which audit committees are engaged in auditor planning, the study's results, by way of a Critical Discourse Analysis of CGRs, contrast with Beattie et al (), who found that audit committees were not satisfactorily engaged in auditor planning. In Beattie et al (), the audit committee chair has specific monitoring responsibilities over the CFO and auditor, but in the narratives presented in the CGRs studied the audit committee chair is not delineated as having specific prominence in the auditor and audit committee interactions. Instead, such interactions in these Swedish companies are disclosed as taking place between the whole audit committee and the auditor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that controlling owners may not have the same agenda as other shareholders (Yeh & Woidtke, ), and large shareholders in the audit committee may influence other members (Bédard & Gendron, ). This may become even more important if UK practices—in which the audit committee chair is gaining increased importance in monitoring the external audit (Beattie et al, )—spread into national contexts marked by concentrated ownership. Future studies are thus warranted of the audit committee composition, particularly regarding the independence of the audit committee chair from large owners, in such national contexts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations